The long-run and short-run exchange rate pass-through during the period of economic reforms in Nigeria: Is it complete or incomplete? - Balcilar, Mehmet; Usman, Ojonugwa; Musa, Muhammad Sani (Institute for Economic Forecasting rjef@ipe.ro, 2020)
This study investigates the long-run and short-run exchange rate pass-through (ERPT) to inflation in Nigeria during the period of economic reforms by incorporating structural breaks over the period 2000Q1-2017Q4. We applied the minimum Lagrange multiplier unit root test with a structural break, the Bayer-Hanck combined cointegration test and the estimation procedure based on the autoregressive distributed lag (ARDL) model. The empirical results suggest that the long-run and short-run ERPT during this period is incomplete with the long-run pass-through having a stronger effect. This confirms the monetary model of short-run price stickiness. The results further divulge that output growth stimulates inflation while oil price dampens inflation in the long run and short run respectively. The effects of trade openness on inflation both in the long run and short run are positive, which cast doubt on the validity of Romer’s (1993) hypothesis. The deviation from the long-run equilibrium level is corrected by 47.6% speed of adjustment in every quarter. These findings, therefore, provide insights for the policymakers to understand the form and scale of ERPT and use its estimated size as a tool to attain low level of inflation and price stability in Nigeria. © 2020, Institute for Economic Forecasting. All rights reserved.
Keywords: ARDL model; Combined cointegration; ERPT; Inflation; Nigeria; Romer’s hypothesis